Early lateral preferences and mental processing trends in black preschoolers. - Jansen, Carmel Patricia (My University, 1998)
The current study adopts a developmental neuropsychological perspective, an approach which does not imply brain dysfunction but rather the principle of understanding the general relationship hetween brain growth and behavioural changes and the effect of environmental factors in children. A neuropsychology of normal development would seem to be an appropriate initial prerequisite if we are to understand the effects of brain insult or disease in the developing child. A modest aim was to acquire a fundamental understanding of emerging skills in black preschool children, starting with the most basic, the development of lateral preferences. This area was selected (a) as a departure point because of its location within the broad area of cerebrallateralization and (b) the opportunity it provided to explore the children's mental processing skills within the same theoretical perspective. The purpose of the present study was the longitudinal investigation of lateral preferences in a sample of Soweto children at three and five years.and information processing skills in the same sample at five years. Three hundred and thirty-five children, 170 girls and 165 boys, were sampled with the assistance of the Birth to Ten project.a longitudinal study of growth, health and development of children living in the Johannesburg Metropolitan area over a ten year period, 1990 to 2000. The children were assessed prior to starting school in January, 1996. A descriptive approach was adopted in explaining the patterns of handedness, footedness and eyeness. The findings showed that the patterns for handedness reflected the expected rightward direction at both ages although the degree to which preference has oeen established was weaker at five years than that reported in other studies with children of similar ages. Thirty-nine percent of the sample were mixed-handed at five years,only 3% were mixed-footed and 5% showed mixed-eyeness, At five years Simultaneous and Sequential information processing skills were assessed with the Kaufman Assessment Battery for Children (K-ABC). Factor analysis revealed a two factor solution broadly supporting the presence of the two processing styles. However the two coding processes were differentially distributed throughout the sample showing significant differences. More specifically.it was found that 34% of the children presented profiles of both processing styles that were below the group mean;31 % showed profiles where one or other coding style was below the group mean;23 % of the children portrayed processing profiles above the group mean. Thirty-nine children (12 %) presented patterns of processing that were above the group mean but were highly developed in one or other processing style. Each of the profiles that emerged were grouped and considered separately. Cognitive tasks involving verbal fluency, naming skills,draw-a person,basic perceptual knowledge,basic literacy.plus lateral preference information such as handedness direction, handedness consistency and handedness skills were appended to all the groups. Low scores in processing styles were found to be associated with poor verbal skills, low mental age,poor perceptual and basic literacy knowledge,poor hand skill performance,and greater (but nonsignificant) numbers of mixed-handers. The lowest scoring group also contained the majority of male left-handers. One of the highest scoring groups showed the strongest lateralizing patterns although the numbers were small (n= 11). Girls with above average sequential skills also scored highly on verbal fluency (p < .05) and hand skills (p < .05). Boys in this group showed the strongest degree of right-handedness (p < .05). In the four lower performance groups,background variables such as type of preschool experience (p <.001),the presence of books in the home (p < .05) and mothers level of education (p <.001) were found to be significant. A regression model which incorporated environmental, epigenetic, cognitive and motoric factors was found to be the most viable in predicting processing skills.
A Thesis submitted to the Faculty of Arts, University of the Witwatersrand in fulfilment of the requirements for the Degree of Doctor of Philosophy
Keywords: Blacks -- Education -- South Africa.; Education, Preschool; Nursery schools -- South Africa.